The Influence of Financial Literacy and Financial Inclusion on The Performance of Msmes in Kediri City - Dika Dimas Putra; Afif Nur Rahmadi; Angga Rizka Lidiawan (PT. Maju Malaqbi Makkarana, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia's economy, yet many face challenges such as limited capital, inadequate financial literacy, and restricted access to financial services, which hinder their growth and competitiveness. This study aims to analyze the influence of financial literacy and financial inclusion on MSME performance in Kediri City, focusing on entrepreneurs who received government capital assistance in 2024. Using a quantitative approach, data were collected from 100 MSME owners through purposive sampling, with questionnaires as the primary instrument. Statistical analyses, including multiple linear regression, t-tests, F-tests, and classical assumption tests, were conducted using SPSS 24. The results reveal that both financial literacy and financial inclusion have positive and significant effects on MSME performance, with the two variables jointly explaining 71% of performance variation. These findings indicate that improving financial knowledge and expanding access to financial services can substantially enhance MSME productivity, competitiveness, and sustainability. The study highlights the importance of targeted financial education and inclusive financial policies to strengthen the resilience and long-term growth of MSMEs in regional economies